Qualitative Phytochemical Analysis and Assessments of Analgesic and Antidiarrheal Activity of the Methanolic Leaf Extract of Cheilanthes tenuifolia: In Vivo Study - Asraful Islam Rakib; Raihan Chowdhury; Md. Shimul Bhuia; Md. Sakib Al Hasan; Salehin Sheikh; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (Immunity, Inflammation and Disease)
ABSTRACT Background Cheilanthes tenuifolia (Burm.f.), commonly known as the Sword Fern or Narrow‐leaved Cloak Fern, is a little evergreen fern that belongs to the Pteridaceae family and is abundant in various bioactive compounds exerting promising medicinal properties. The current study is designed to evaluate in vivo analgesic and antidiarrheal activity of the methanol leaf extract of C. tenuifolia (MCT). Methods For this purpose, Swiss albino mice were used to investigate the analgesic and antidiarrheal properties using acetic acid‐induced writhing and castor oil‐induced diarrhea methods, respectively. The mice were administered orally with different doses of MCT (125, 250, and 500 mg/kg). The vehicle performed as a negative control (NC), while diclofenac sodium (DCN) (25 mg/kg), loperamide (LOP) (3 mg/kg), bismuth subsalicylate (BSS) (10 mg/kg), and nifedipine (NDP) (2.5 mg/kg) were supplied as positive controls (PC) (p.o.). In both models, combination treatment of MCT (higher dose) and PC was also administered to different groups of animals for assessing potential antagonistic or synergistic activity. Results Findings of the in vivo study demonstrated that MCT dose‐dependently significantly (p < 0.05) exhibited analgesic and antidiarrheal properties by reduction in the number of writhing and reductions in the total fecal output in contrast to the NC group. Moreover, in combination treatment, MCT significantly (p < 0.05) synergized the activity of PC in both models, exerting potential analgesic and antidiarrheal activity. Conclusion In conclusion, MCT has analgesic and antidiarrheal activity; it might be beneficial for the management of pain and diarrhea.